Lux Meter Sebagai Alat Ukur Intensitas Cahaya Lampu Operasi Berbasis Arduino Uno R3 - Nur Hudha Wijaya; Sutrimo Sutrimo (Jurusan Teknik Elektro, Universitas Bangka Belitung, 2021)
The light in the operating room has a special luminance intensity standard, so the light intensity needs to be known, because it adapts to lighting needs and functions. The lamps used for operating lighting must meet the requirements stipulated by law, good lighting is lighting that suits your needs, for operating rooms that are 300-500 lux and for operating tables 10,000-20,000 Lux. The problem in the field is that not all hospitals have a lux meter measuring instrument, so when taking measurements if there is an unsuitability of the light it brings a third party, from the problem so that it is not dependent, the research method used is the experimental method, with Arduino uno R3 programming. The Lux meter that has been made has been successful and has been tested with a calibration tool, in this case the calibration test is carried out in the hospital. Based on the calibration test data shows quite good results, the measurement data has been tested 20 times with a distance of 1 meter and 20 times at a distance of 1.5 meters. Based on the measurement and comparison of data, it can be concluded that the error of the tool is relatively low, namely 0.01% at a distance of 1 meter with a difference of 2 lux, and an error value of 0.23% at a distance of 1.5 meters with a difference of 24 lux. For distance measurement and timer, the error is 0% so that it has a difference of 0%.